Biogeographic barriers in the circulation and interaction of hunter-gatherer marine fishers: The role of the Taitao Peninsula and the Gulf of Penas (∼ 47°S) in the differentiation of the cultural trajectories of West Patagonia - Reyes, Omar; Méndez, César; San Román, Manuel; Belmar, Carolina; Nuevo-Delaunay, Amalia (Frontiers in Earth Science, 2022)
Archaeological research on the settlement of the Patagonian archipelago in the extreme south of South America by groups of hunter-gatherers, fishers or canoeists involves both an understanding of the various modes of subsistence and the possible flows of goods and human interactions that could have occurred over time in this extensive territory. Therefore, the study of how the geographical barriers that occur in western Patagonia operated is fundamental because it allows evaluating and discussing not only the characteristics and particularities of the occupation of the archipelagic territory but also its role in the circulation and contact of canoe populations, their relevance in the settlement and occupation of the Patagonian archipelago and their possible impact on the differentiation of the cultural trajectories of the canoe groups that inhabited it. We review and discuss the archaeological record of the areas adjacent to the geographical barrier formed by the Taitao Peninsula and the northeastern and southern coast of the Gulf of Penas (47° S) in west Patagonia. This extensive geographical area acted as a permeable barrier, conditioning, over time, maritime mobility and circulation routes, channeling or limiting the access and contact between the canoe groups on both sides of it.